Essays on Labour Economics - Cui, Jing (Université d'Ottawa / University of Ottawa, 2025)
The first chapter studies the labour force participation of older individuals during COVID-19. COVID-19 significantly changed the labour participation rates of older Canadians, leading to substantial flows among employment, unemployment, marginal attachment, and non-attachment. Using the Canadian Labour Force Survey (LFS), this paper examines the impact of these flows on the participation rates of older individuals and explores whether COVID-19 prompted early retirements. Unlike the Great Recession, the pandemic caused significant direct separations from employment to non-participation. Additionally, older women experienced slower participation rate recovery than men due to higher outflows and lower inflows. Notably, many individuals who initially became non-attached to the labour force in early 2020 transitioned back to employment in the following months of the same year. Generally, the pandemic did not increase older individuals' self-reported retirement transitions and reduced their probability of staying non-attached to the labour market. The second chapter examines the cyclicality of worker flows across experience levels in Canada. Using the LFS, I estimate individual monthly transition probabilities over business cycles conditional on labour-market experience and job tenure. The job-finding rate and separation rate are relatively more cyclical for the youth. I find that experience is a major contributor to the cyclical fluctuations in employer-to-employer probabilities, whereas tenure is a major contributor to the cyclicality of employment-to-nonemployment. The third chapter studies the evolution of the gender unemployment gap in Canada. The gender unemployment gap - defined as women's unemployment rates minus men's unemployment rates - was positive before 1990 but has remained negative since then. I decompose the gender unemployment gap into contributions from gender differences in transition flows between employment, unemployment, and non-participation. The results show that gender differences in flows between employment and non-participation have been positive contributors to the gap over time, while gender differences in employment-to-unemployment flows have been a significant negative contributor. Over the decades, the contribution of flows between employment and non-participation has been decreasing. As employment-to-unemployment flows continue to contribute negatively to the gap, the diminishing contribution of flows between employment and non-participation explains the flip of the gender unemployment gap from positive to negative. Furthermore, I find that differences in industry and occupation composition play a significant role in explaining the gender difference in employment-to-unemployment transition rates.
Keywords: COVID-19; unemployment; retirement transition; job transitions; business cycles; labour force participation; job tenure; gender gaps; Canadian Labour Force Survey; stock-flow decomposition